Identification of electro-hydraulic actuator using fractional model - Yusof, N. M. (Massey University, 2016)
Electro-hydraulic actuator (EHA system) identification is to describe the characteristic of the system that useful for prediction or control system design. There are numerous methods of EHA modeling but there has not been much model using fractional-order (FO) model. In this work, integer-order (IO) model and FO model are developed to model EHA system. Output-error method is used as the estimator for both model. The coefficient of IO model was first estimated and using the estimated coefficient, the derivative order of FO model is estimated. These models has been validated by comparison of error, coefficient of determination (R2), mean square error (MSE) and correlation function. The results for the proposed model show improvement compared to the IO model.